Key factors affecting rail service quality in the Northern Italy: a decision tree approach - De Oña, Rocío; Eboli, Laura; Mazzulla, Gabriella (Transport, 2014)
This work concerns with the analysis of transit service quality on the basis of the perceptions directly expressed by the passengers of the services. The transit services supporting the research are offered by rail operators of the Northern Italy, and particularly by regional and suburban lines connecting different towns of the hinterland of the city of Milan, and express lines connecting Milan with the Malpensa airport. The experimental data were collected in a survey conducted in May 2012, and addressed to a sample of more than 16,000 passengers. Passengers expressed their opinions about service characteristics such as safety, cleanliness, comfort, information, personnel. The tool chosen for evaluating service quality is a Classification and Regression Tree Approach (CART), useful for identifying the characteristics mostly influencing the overall service quality. We found that service characteristics like ‘Windows and Doors Working’, ‘Courtesy and Competence on Board’, ‘Information at Stations’, ‘Punctuality of Runs’, ‘Courtesy and Competence in Station’ and ‘Regularity of Runs’ mainly influence service quality. First Published Online: 25 Mar 2014